Effect of load models on angular and frequency stability of low inertia power networks. Issue 9 (5th April 2019) - Adrees, Atia; Milanović, Jovica
Abstract : This study presents a thorough analysis of the effect of load models on frequency response, small and large disturbance stability of the power system, in order to identify the type of stability exhibiting most sensitivity to load models, and for each type of studied stability to pinpoint the load model that has the worst effect. The presented analysis shows clearly that transient stability is the most sensitive to load models. The number of unstable cases varies considerably with each type of studied load model. The effect of the load model magnifies with the reduction in headroom of synchronous generators. The results of frequency response of the system following an active power disturbance demonstrate that the influence of constant power loads can be significant if the system is operating with reduced primary frequency response at high load. High integration of renewable energy sources (RES) increases the variation in the damping of electromechanical modes due to increased uncertainties, and a high proportion of induction machines can reduce the damping of inter‐area modes considerably, making a well stable mode unstable for certain operating points. The influence of load models has been illustrated using a 68‐bus system with 30% and 52% penetration of RES.